Aluminum hydride material doped with high-entropy MXene and preparation method, hydrogen release method and application thereof
Patent Information
- Application Number
- CN202611161170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
本申请实施例提供的掺杂高熵MXene的铝氢化物材料,通过将高熵MXene催化剂组分引入铝氢化物释氢体系,并使高熵MXene催化剂组分至少部分分布于铝氢化物组分的颗粒表面、颗粒间隙、晶粒边界或界面区域,高熵MXene催化剂组分与铝氢化物组分形成球磨复合、表面复合、界面复合、包覆复合或成型复合,提高催化界面接触质量,从而利用高熵MXene的多金属位点、二维层状结构、表面端基、导电界面和界面浸润作用,实现铝氢化物热分解及热分解产物水解供氢的连续高效利用。具体的,在热分解阶段,高熵MXene催化剂组分可促进铝氢化物中Al-H键的活化与断裂,降低热分解温度并提高供氢速率;在水解供氢阶段,热分解产物中的金属氢化物与水反应生成氢气和碱性产物,所形成的碱性环境能够促进金属铝表面钝化层破坏或溶解,使金属铝进一步参与水解产氢,获得热分解与热分解产物水解供氢相结合的高效供氢效果。本申请的掺杂高熵MXene的铝氢化物材料既能改善铝氢化物低温热分解性能,又能利用热分解后的产物继续通过注水或含水反应介质水解供氢,从而提高铝氢化物中可利用氢的释放程度和实际供氢应用价值,解决了现有铝氢化物体系存在的热分解温度较高、动力学较慢、产物利用不足以及单一催化体系难以同时兼顾热分解和热分解产物水解供氢的问题。
Smart Images

Figure CN122977314A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of solid-state hydrogen storage technology, specifically relating to an aluminum hydride material doped with high-entropy MXene, its preparation method, hydrogen release method, and application. Background Technology
[0002] Hydrogen energy, as a clean and efficient secondary energy source, boasts advantages such as high mass energy density, diverse utilization methods, and clean byproducts. Compared to high-pressure gaseous hydrogen storage and cryogenic liquid hydrogen storage, solid-state hydrogen storage materials can achieve higher volumetric hydrogen storage density and better safety under relatively mild conditions, making them an important technological direction for fuel cell hydrogen supply, portable hydrogen power sources, emergency hydrogen supply, and distributed energy systems.
[0003] Aluminum hydrides are important materials for solid-state hydrogen storage and chemical hydrogen supply. Among them, LiAlH4, NaAlH4, AlH3, Mg(AlH4)2, and Ca(AlH4)2 have high theoretical hydrogen contents and can release hydrogen through thermal decomposition. Taking LiAlH4 as an example, it can release hydrogen through stepwise thermal decomposition, but in practical applications, it usually suffers from problems such as high initial decomposition temperature, slow kinetics, insufficient low-temperature decomposition, difficulty in finely controlling the thermal decomposition process, and insufficient exploitation of usable hydrogen in the thermal decomposition products.
[0004] In existing technologies, transition metals, metal oxides, metal halides, metal carbides, carbon materials, common MXenes, and their supported composite catalysts have been used to improve the thermal decomposition performance of aluminum hydrides. These technologies typically focus on lowering the thermal decomposition temperature of aluminum hydrides, increasing the thermal decomposition rate, or improving the hydrogen release at a given temperature. However, for some aluminum hydrides, the products of thermal decomposition often contain residual metal hydrides, metallic aluminum, or other hydrolyzable components. If these products are not further utilized, it will lead to insufficient utilization of the system's releaseable hydrogen.
[0005] Therefore, there is an urgent need to provide an aluminum hydride composite material that can improve the low-temperature thermal decomposition performance of aluminum hydrides and utilize the products after thermal decomposition to continue hydrolyzing and supplying hydrogen, thereby increasing the release of usable hydrogen from aluminum hydrides and its practical hydrogen supply application value. Summary of the Invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.
[0007] Therefore, a first aspect of the present invention provides an aluminum hydride material doped with high-entropy MXene.
[0008] A second aspect of the present invention provides a method for preparing an aluminum hydride material doped with high-entropy MXene.
[0009] A third aspect of the present invention provides a method for releasing hydrogen from an aluminum hydride material doped with high-entropy MXene.
[0010] A fourth aspect of the present invention provides an application of an aluminum hydride material doped with high-entropy MXene.
[0011] In view of this, a first aspect of the embodiments of this application provides an aluminum hydride material doped with high-entropy MXene, comprising: The aluminum hydride component and the high-entropy MXene catalyst component are present. The high-entropy MXene catalyst component is at least partially distributed on the particle surface, interparticle space, grain boundary or interface region of the aluminum hydride component. The high-entropy MXene catalyst component and the aluminum hydride component form a physical composite. The high-entropy MXene catalyst component is used to promote the activation and breaking of Al-H bonds during the thermal decomposition of the aluminum hydride component, and to promote the hydrolysis and hydrogen supply of the thermal decomposition products after contact with water or an aqueous reaction medium. Physical composites include at least one of ball milling composites, surface composites, interface composites, coating composites, embedding composites, slurry composites, granulation composites, and molding composites.
[0012] In one feasible implementation, the high-entropy MXene catalyst component is a multilayer sheet structure, a few-layer sheet structure, a single-layer sheet structure, an accordion-like layer structure, a peeled sheet structure, a wrinkled sheet structure, a nanosheet stacked structure, or a porous sheet structure.
[0013] In one feasible implementation, the chemical formula of the high-entropy MXene catalyst component is represented as M. n+1 X n T x ; Wherein, M is a metal site element, and M is selected from at least four of the metal elements in Groups IIIB, IVB, VB, VIB, VIIB, VIII, IB and IIB of the periodic table and the lanthanide metal elements; X is a combination of one or more of C, N and B; T x For surface end bases, T x It is a combination of one or more of O, F, Cl, Br, I and OH; n can be 1, 2, 3, 4, 5, or 6.
[0014] In one feasible implementation, M includes at least four of the following: Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, Au, Zn, Cd, and lanthanide metals.
[0015] In one feasible embodiment, the aluminum hydride component includes at least one of LiAlH4, NaAlH4, AlH3, Li3AlH6, Na3AlH6, and Mg(AlH4)2; The high-entropy MXene catalyst components include M2CT x Model, M3C2T x Type, M4C3T x Model, M5C4T x Type, M2NT x Type, M3N2T x Type and M2BT x At least one of the types; The mass percentage of the high-entropy MXene catalyst component relative to the aluminum hydride component is 0.1 wt.% to 50 wt.%.
[0016] According to a second aspect of the embodiments of this application, a method for preparing a high-entropy MXene-doped aluminum hydride material is provided, for preparing a high-entropy MXene-doped aluminum hydride material as described in any of the above technical solutions, comprising: Post-processing of high-entropy MXene catalyst components; In an inert atmosphere, vacuum, or low-water, low-oxygen environment, the aluminum hydride component is mixed with the high-entropy MXene catalyst component to obtain a mixture; The mixture is subjected to physical composite treatment so that the high-entropy MXene catalyst component is at least partially distributed on the particle surface, interparticle gaps, grain boundaries or interface regions of the aluminum hydride component. Among them, physical composite processing includes at least one of mechanical ball milling, grinding, mixing, kneading, shearing dispersion, granulation, tableting, rolling and molding processes.
[0017] In one feasible implementation, the step of further steps, prior to post-processing the high-entropy MXene catalyst component, includes: Provide high-entropy MAX phase precursors or high-entropy MXene catalyst components; When a high-entropy MAX phase precursor is provided, the high-entropy MAX phase precursor is selectively etched to remove at least some of the A-layer elements to obtain the high-entropy MXene catalyst component. Selective etching processes include at least one of HF etching, HCl / LiF etching, fluoride / acid system etching, molten salt etching, alkaline etching, oxidative etching, and electrochemical etching.
[0018] In one feasible implementation, In low-water and low-oxygen environments, the water content is below 1000 ppm and the oxygen content is below 1000 ppm. When physical composite treatment includes mechanical ball milling, the ball-to-material ratio is (5~100):1, the ball milling speed is 100r / min~800r / min, and the ball milling time is 0.1h~24h.
[0019] According to a third aspect of the embodiments of this application, a method for releasing hydrogen from a high-entropy MXene-doped aluminum hydride material is proposed, applicable to aluminum hydride materials doped with high-entropy MXene as described in any of the above technical solutions, comprising: In the thermal decomposition and hydrogen release stage of the material, the material is placed in a reactor and heated under inert atmosphere, vacuum, low pressure, normal pressure or set back pressure conditions to cause the aluminum hydride components to undergo thermal decomposition and release hydrogen gas, and obtain thermal decomposition products. During the hydrogen supply stage of hydrolysis of thermal decomposition products, water or an aqueous reaction medium is added to the thermal decomposition products to hydrolyze the metal hydrides and / or aluminum in the thermal decomposition products and release hydrogen gas.
[0020] According to a fourth aspect of the embodiments of this application, an application of an aluminum hydride material doped with high-entropy MXene is proposed. The aluminum hydride material doped with high-entropy MXene based on any of the above technical solutions includes: The material is used as a powder hydrogen storage material, catalytic hydrogen storage material, molded hydrogen storage material, hydrogen supply filler, water injection hydrogen production fuel pellet, hydrogen supply module or hydrogen source unit.
[0021] This application discloses an aluminum hydride material doped with high-entropy MXene, its preparation method, hydrogen release method, and application. Compared with existing technologies, the advantages are as follows: The aluminum hydride material doped with high-entropy MXene provided in this application introduces the high-entropy MXene catalyst component into the aluminum hydride hydrogen release system, and at least partially distributes the high-entropy MXene catalyst component on the particle surface, interparticle gaps, grain boundaries, or interface regions of the aluminum hydride component. The high-entropy MXene catalyst component and the aluminum hydride component form ball-milled composites, surface composites, interface composites, coating composites, or molding composites, thereby improving the catalytic interface contact quality. Thus, by utilizing the multi-metal sites, two-dimensional layered structure, surface end groups, conductive interfaces, and interface wetting effect of high-entropy MXene, the continuous and efficient utilization of aluminum hydride thermal decomposition and hydrolysis of thermal decomposition products for hydrogen supply is achieved. Specifically, in the thermal decomposition stage, the high-entropy MXene catalyst component can promote the activation and breaking of Al-H bonds in aluminum hydrides, reducing the thermal decomposition temperature and increasing the hydrogen supply rate. In the hydrolysis hydrogen supply stage, the metal hydrides in the thermal decomposition products react with water to generate hydrogen and alkaline products. The resulting alkaline environment can promote the destruction or dissolution of the passivation layer on the surface of the aluminum metal, allowing the aluminum metal to further participate in hydrolysis to produce hydrogen, thus achieving a highly efficient hydrogen supply effect combining thermal decomposition and hydrolysis hydrogen supply from thermal decomposition products. The aluminum hydride material doped with high-entropy MXene in this application can not only improve the low-temperature thermal decomposition performance of aluminum hydrides, but also utilize the products after thermal decomposition to continue hydrolysis hydrogen supply through water injection or aqueous reaction media, thereby increasing the release of usable hydrogen in aluminum hydrides and its practical hydrogen supply application value. This solves the problems of high thermal decomposition temperature, slow kinetics, insufficient product utilization, and the difficulty of a single catalytic system simultaneously addressing thermal decomposition and hydrolysis hydrogen supply from thermal decomposition products in existing aluminum hydride systems. Attached Figure Description
[0022] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 A scanning electron microscope image of an aluminum hydride material doped with high-entropy MXene, provided in this application; Figure 2 A schematic flowchart illustrating the steps of a method for preparing a doped high-entropy MXene aluminum hydride material according to an embodiment of this application; Figure 3 Scanning electron microscope image of high-entropy MXene prepared by a method for preparing doped high-entropy MXene aluminum hydride material according to an embodiment of this application; Figure 4 Temperature-programmed dehydrogenation curves for undoped, doped conventional MXene, and high-entropy MXene LiAlH4 composite powders; Figure 5Temperature-programmed dehydrogenation curves of undoped, high-entropy MXene LiAlH4 composite powder and hydrolysis dehydrogenation curves of the product. Detailed Implementation
[0023] In the description of this application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.
[0024] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0025] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0026] The preferred embodiments of this application are described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit this application.
[0027] like Figure 1As shown, according to a first aspect of the embodiments of this application, an aluminum hydride material doped with high-entropy MXene is proposed, comprising: an aluminum hydride component and a high-entropy MXene catalyst component, wherein the high-entropy MXene catalyst component is at least partially distributed on the particle surface, interparticle gaps, grain boundaries, or interface regions of the aluminum hydride component, and the high-entropy MXene catalyst component forms a physical composite with the aluminum hydride component, wherein the high-entropy MXene catalyst component is used to promote the activation and breaking of Al-H bonds during the thermal decomposition of the aluminum hydride component, and to promote the hydrolysis and hydrogen donation of the thermal decomposition products after contact with water or an aqueous reaction medium; wherein, the physical composite includes at least one of ball milling composite, surface composite, interface composite, coating composite, embedding composite, slurry composite, granulation composite, and molding composite.
[0028] The aluminum hydride material doped with high-entropy MXene provided in this application introduces the high-entropy MXene catalyst component into the aluminum hydride hydrogen release system, and at least partially distributes the high-entropy MXene catalyst component on the particle surface, interparticle gaps, grain boundaries, or interface regions of the aluminum hydride component. The high-entropy MXene catalyst component and the aluminum hydride component form ball-milled composites, surface composites, interface composites, coating composites, or molding composites, thereby improving the catalytic interface contact quality. Thus, by utilizing the multi-metal sites, two-dimensional layered structure, surface end groups, conductive interfaces, and interface wetting effect of high-entropy MXene, the continuous and efficient utilization of aluminum hydride thermal decomposition and hydrolysis of thermal decomposition products for hydrogen supply is achieved. Specifically, in the thermal decomposition stage, the high-entropy MXene catalyst component can promote the activation and breaking of Al-H bonds in aluminum hydrides, reducing the thermal decomposition temperature and increasing the hydrogen supply rate. In the hydrolysis hydrogen supply stage, the metal hydrides in the thermal decomposition products react with water to generate hydrogen and alkaline products. The resulting alkaline environment can promote the destruction or dissolution of the passivation layer on the surface of the aluminum metal, allowing the aluminum metal to further participate in hydrolysis to produce hydrogen, thus achieving a highly efficient hydrogen supply effect combining thermal decomposition and hydrolysis hydrogen supply from thermal decomposition products. The aluminum hydride material doped with high-entropy MXene in this application can not only improve the low-temperature thermal decomposition performance of aluminum hydrides, but also utilize the products after thermal decomposition to continue hydrolysis hydrogen supply through water injection or aqueous reaction media, thereby increasing the release of usable hydrogen in aluminum hydrides and its practical hydrogen supply application value. This solves the problems of high thermal decomposition temperature, slow kinetics, insufficient product utilization, and the difficulty of a single catalytic system simultaneously addressing thermal decomposition and hydrolysis hydrogen supply from thermal decomposition products in existing aluminum hydride systems.
[0029] It should be noted that hydrolysis for hydrogen production technology utilizes the reaction of metal hydrides or active metals with water to release hydrogen gas. For aluminum hydrides such as LiAlH4, the products of thermal decomposition of LiAlH4 often contain LiH, Al, or other hydrolyzable components; LiH can react with H2O to generate LiOH and H2; Al can also further participate in hydrolysis for hydrogen production under alkaline conditions or suitable interfacial conditions.
[0030] The inventors discovered that, for aluminum hydride materials, if the hydrogen release from the initial thermal decomposition and the hydrogen supply from the hydrolysis of subsequent thermal decomposition products can be synergistically designed, the hydrogen that can be released at different stages in the aluminum hydride material can be continuously utilized. MXenes are two-dimensional materials composed of transition metal carbides, nitrides, carbonitrides, or borides, possessing a layered structure, good electrical conductivity, surface end groups, and tunable interfacial chemistry. Common MXenes include Ti3C2T. x Ti2CT x While existing metals have shown catalytic potential in hydrogen storage and water splitting for hydrogen production, their metal sites are relatively singular or have few components, resulting in limited local electronic structures and active site types. High-entropy MXenes, on the other hand, have multiple metal elements occupying the M site, providing a richer local coordination environment, a wider electronic structure regulation space, more types of metal active sites, and tunable surface end-group structures.
[0031] In one feasible implementation, the high-entropy MXene catalyst component is a multilayer sheet structure, a few-layer sheet structure, a single-layer sheet structure, an accordion-like layer structure, a peeled sheet structure, a wrinkled sheet structure, a nanosheet stacked structure, or a porous sheet structure.
[0032] In this technical solution, the high-entropy MXene catalyst comprises multilayer sheet structures, few-layer sheet structures, single-layer sheet structures, accordion-like layered structures, exfoliated sheet structures, wrinkled sheet structures, nanosheet stacked structures, or porous sheet structures. This gives the high-entropy MXene a two-dimensional sheet structure and layered mass transfer channels, enabling it to form a fully contacting catalytic interface with aluminum hydrides, thus improving the quality of the catalytic interface contact. Simultaneously, the two-dimensional sheet structure provides abundant exposed surfaces for active sites and interlayer mass transfer channels, promoting water molecule adsorption and the hydrolysis of thermal decomposition products, thereby balancing hydrogen supply from thermal decomposition and hydrolysis. By selecting different sheet structure types, the specific surface area, interlayer spacing, defect density, and active site exposure of the high-entropy MXene catalyst can be flexibly controlled according to the specific aluminum hydride type, application scenario, and performance requirements, achieving optimized control of catalytic performance.
[0033] Specifically, multilayered sheet structures and accordion-like layered structures possess large interlayer spaces and abundant interlayer channels, accommodating aluminum hydride components or their decomposition products for reaction and mass transfer within the layers, thus improving the contact area and reaction efficiency of the catalytic interface. Few-layered sheet structures and monolayered sheet structures have extremely high specific surface areas and fully exposed active sites, thereby maximizing the catalytic effect of multi-metal sites, effectively reducing the thermal decomposition temperature of aluminum hydrides and increasing the hydrogen donation rate. Exfoliated sheet structures and wrinkled sheet structures have abundant edge and defect sites, serving as preferential reaction centers for Al-H bond activation, which helps to lower the activation energy of the thermal decomposition reaction. Nanosheet stacked structures and porous sheet structures combine high specific surface areas with good structural stability, effectively preventing the aggregation of nanosheets during composite and reaction processes while ensuring catalytic activity, maintaining the long-term stability of the catalytic interface.
[0034] In one feasible implementation, the chemical formula of the high-entropy MXene catalyst component is represented as M. n+1 X n T x Where M is the metal site element, selected from at least four metals in Groups IIIB, IVB, VB, VIB, VIIB, VIII, IB, and IIB of the periodic table, as well as lanthanide metals; X is one or more combinations of C, N, and B; Tx is the surface end group, T... x It is a combination of one or more of O, F, Cl, Br, I and OH; n is 1, 2, 3, 4, 5 or 6.
[0035] In this technical solution, the chemical formula of high-entropy MXene is M n+1 X n T x The M site is selected from at least four metals from Groups IIIB to IIB of the periodic table and lanthanides, achieving a synergistic catalytic effect of multiple metal sites. Multiple metal elements jointly occupy the M site, forming a multi-principal solid solution and localized multi-metal coordination environment. Constructing multi-metal M sites through combinations of metals from multiple groups in the periodic table improves the catalyst composition design space and active site regulation space. The X site is one or more combinations of C, N, and B. The lattice structure, electronic properties, and chemical stability of MXene can be regulated through the selection and combination of elements at the X site; the surface end group T... xMXenes can be selected from one or more combinations of O, F, Cl, Br, I, and OH groups. By choosing and combining different end groups, the surface chemical properties, hydrophilicity / hydrophobicity, and interfacial wettability can be controlled. Furthermore, by selecting different n values, the number of atomic layers and interlayer spacing of MXenes can be controlled. A smaller n value results in a thinner atomic layer thickness and a higher specific surface area, which is beneficial for the exposure of active sites; a larger n value results in more atomic layers and more abundant interlayer space, which is beneficial for interlayer transport and reactions.
[0036] It should be noted that the term "high-entropy MXene" in this application is not limited to a strict equimolar ratio. As long as the M site contains at least four metal elements and forms a multi-principal solid solution, localized multi-metal coordination, two-dimensional layered MXene structure or its derivative structure, it can be used as a component of the high-entropy MXene catalyst described in this application.
[0037] In one feasible implementation, M includes at least four of the following: Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, Au, Zn, Cd, and lanthanide metals.
[0038] In this technical solution, the M sites of high-entropy MXene are limited to at least four of the following: Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, Au, Zn, Cd, and lanthanide metals. This further clarifies the specific composition range of the multi-metal M sites. These metal elements have different atomic radii, electronegativity, and electronic configurations. The combination of multiple metal elements can form a multi-principal solid solution and local multi-metal coordination environment at the M sites of MXene, producing lattice distortion and electronic structure regulation effects, thereby providing richer catalytic active sites and better electron transfer capabilities.
[0039] Furthermore, when M is selected from at least four of Ti, V, Cr, Nb, Mo, Ta, Zr, Hf, W, Fe, Co, and Ni, a more preferred combination of catalytic performance can be obtained. When the high-entropy MXene catalyst component is a Ti-V-Cr-Nb-Mo system, a Ti-V-Nb-Mo-Ta system, a Ti-Zr-Hf-Nb-Ta system, a Ti-V-Cr-Mo-W system, a Ti-V-Fe-Co-Ni system, or a Ti-V-Cr-Nb-Mo-Ta system, the catalytic effect on the thermal decomposition and hydrolysis hydrogen donation of aluminum hydrides is better. For example, the Ti-V-Cr-Nb-Mo system M2CT... xAfter high-entropy MXene is doped with LiAlH4, it can achieve low-temperature thermal decomposition under heating conditions, and the products after thermal decomposition can be used for subsequent hydrolysis to supply hydrogen.
[0040] In one feasible embodiment, the aluminum hydride component includes at least one selected from LiAlH4, NaAlH4, AlH3, Li3AlH6, Na3AlH6, and Mg(AlH4)2; the high-entropy MXene catalyst component includes M2CT. x Model, M3C2T x Type, M4C3T x Model, M5C4T x Type, M2NT x Type, M3N2T x Type and M2BT x At least one of the types; the mass percentage of the high-entropy MXene catalyst component relative to the aluminum hydride component is 0.1 wt.% to 50 wt.%.
[0041] In this technical solution, the aluminum hydride component is at least one of LiAlH4, NaAlH4, AlH3, Li3AlH6, Na3AlH6, and Mg(AlH4)2, suitable for applications with different hydrogen storage capacity requirements and hydrogen release temperature requirements. These aluminum hydrides all have high theoretical hydrogen content and can release hydrogen through thermal decomposition, making them suitable for solid-state hydrogen storage and chemical hydrogen supply. The high-entropy MXene catalyst component has an M2CT structure. x Model, M3C2T x Type, M4C3T x Model, M5C4T x Type, M2NT x Type, M3N2T x Type and M2BT x At least one of the following types allows high-entropy MXenes to have different atomic layer numbers and interlayer spaces. When the mass percentage of the high-entropy MXene catalyst component relative to the aluminum hydride component is less than 0.1 wt.%, there are insufficient catalytic active sites, making it difficult to effectively promote the thermal decomposition and hydrolysis reactions of aluminum hydride. When the mass percentage of the high-entropy MXene catalyst component relative to the aluminum hydride component is greater than 50 wt.%, although the catalytic effect may be further improved, the overall hydrogen content and energy density of the material will be significantly reduced. By controlling the mass percentage of the high-entropy MXene catalyst component relative to the aluminum hydride component within the range of 0.1 wt.% to 50 wt.%, sufficient catalytic effect can be ensured while avoiding a decrease in the overall hydrogen storage capacity of the material due to excessively high catalyst content.
[0042] Specifically, different aluminum hydrides exhibit different decomposition temperatures and pathways. LiAlH4 possesses a high theoretical hydrogen content and stepwise thermal decomposition characteristics; NaAlH4 exhibits good reversible hydrogen absorption and desorption performance and low cost; AlH3 has a theoretical hydrogen content of approximately 10 wt.% and a relatively low decomposition temperature; Li3AlH6 and Na3AlH6 are intermediate products of aluminum hydride thermal decomposition, possessing specific decomposition temperature windows; Mg(AlH4)2 has a high hydrogen content and good thermal stability. Furthermore, when the aluminum hydride composition is LiAlH4, the optimal hydrogen storage capacity and hydrogen release performance can be obtained.
[0043] Furthermore, the mass percentage of the high-entropy MXene catalyst component relative to the aluminum hydride component is preferably 0.5 wt.% to 30 wt.%, more preferably 1 wt.% to 20 wt.%, and even more preferably 2 wt.% to 12 wt.%, which can maintain the high hydrogen storage capacity of the material to the maximum extent while ensuring significant catalytic effect.
[0044] Specifically, M2CT x The M3C2T type has three atomic layers, a relatively simple structure, and a large specific surface area, which is beneficial for the exposure of active sites; x The M4C3T type has 5 atomic layers, resulting in better structural stability and richer interlayer space; x Model and M5C4T x The M2NT type has thicker atomic layers and a more complex interlayer environment, providing more space for interlayer reactions; x Type and M3N2T x The form is MXene, a nitride, with different electronic properties and chemical activities; M2BT x The high-entropy MXene catalyst, a boride, possesses unique structural and performance characteristics. By selecting different structural types, the physicochemical properties of the catalyst can be flexibly controlled.
[0045] Preferably, the high-entropy MXene catalyst component is Ti. 0.4 V 0.4 Cr 0.4 Nb 0.4 Mo 0.4 CT x or Ti 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 C2T x or its derivatives.
[0046] like Figure 2As shown, according to a second aspect of this application, a method for preparing a high-entropy MXene-doped aluminum hydride material is proposed, for preparing a high-entropy MXene-doped aluminum hydride material as described in any of the above technical solutions, comprising: Step 100: Post-processing of the high-entropy MXene catalyst components; Step 200: Under an inert atmosphere, vacuum, or low-water and low-oxygen environment, mix the aluminum hydride component with the high-entropy MXene catalyst component to obtain a mixture; Step 300: Perform physical composite treatment on the mixture so that the high-entropy MXene catalyst component is at least partially distributed on the particle surface, interparticle space, grain boundary or interface region of the aluminum hydride component; Among them, physical composite processing includes at least one of mechanical ball milling, grinding, mixing, kneading, shearing dispersion, granulation, tableting, rolling and molding processes.
[0047] The method for preparing aluminum hydride materials doped with high-entropy MXene provided in this application removes residual etching agents and byproducts from the high-entropy MXene preparation process by washing, centrifuging, filtering, drying, ultrasonically exfoliating, classifying, surface treating, or storing in an inert atmosphere. This process controls the interlayer spacing, lamellar size, surface state, and dispersibility of the catalyst components, which is beneficial for the uniform dispersion of the catalyst and the formation of high-quality interfacial contacts in subsequent composite processes. By mixing the aluminum hydride components with the high-entropy MXene catalyst components under an inert atmosphere, vacuum, or low-water, low-oxygen environment, the decomposition or surface passivation of the aluminum hydride due to contact with moisture and oxygen in the air during the preparation process is avoided, ensuring the activity and purity of the material. By subjecting the resulting mixture to mechanical ball milling, grinding, slurry mixing, kneading, shear dispersion, granulation, tableting, rolling, or molding, the high-entropy MXene catalyst components are at least partially distributed on the surface, interparticle gaps, grain boundaries, or interfacial regions of the aluminum hydride particles, which is beneficial for forming sufficient catalytic contact interfaces and improving the quality of catalytic interfacial contact. High-entropy MXene can not only serve as a catalytic interface for thermal decomposition, but also promote the adsorption of water molecules and the hydrolysis of thermal decomposition products through hydrophilic end groups, defect sites, layered mass transfer channels or multi-metal active sites, thus taking into account both thermal decomposition and hydrolysis hydrogen supply.
[0048] In some examples, aluminum hydride materials doped with high-entropy MXene are granulated, tableted, rolled, or molded to produce powders, granules, tablets, blocks, thin layers, coatings, fuel sheets, or packed bodies suitable for different filling and hydrogen supply methods.
[0049] In one feasible implementation, the step of further steps, prior to post-processing the high-entropy MXene catalyst component, includes: Provide high-entropy MAX phase precursors or high-entropy MXene catalyst components; When a high-entropy MAX phase precursor is provided, the high-entropy MAX phase precursor is selectively etched to remove at least some of the A-layer elements to obtain the high-entropy MXene catalyst component. Selective etching processes include at least one of HF etching, HCl / LiF etching, fluoride / acid system etching, molten salt etching, alkaline etching, oxidative etching, and electrochemical etching.
[0050] In this technical solution, a high-entropy MAX phase precursor can be provided, and at least some A-layer elements can be removed through selective etching to obtain a high-entropy MXene catalyst component with a two-dimensional layered structure; alternatively, the high-entropy MXene catalyst component can be provided directly, offering flexible raw material selection for subsequent composites. When a high-entropy MAX phase precursor is provided, the most suitable etching scheme is selected based on the specific composition of the high-entropy MAX phase, the types of A-layer elements, and etching requirements. Aluminum hydride materials doped with high-entropy MXene can be prepared through processes such as high-entropy MAX phase preparation, selective etching, inert atmosphere ball milling, slurry mixing, granulation, or tableting. The material composition is adjustable, the process path is clear, and it is suitable for laboratory research, scale-up preparation, and engineering development.
[0051] Specifically, HF etching is suitable for etching various MAX phases; HCl / LiF etching is a relatively mild in-situ HF generation method, which can reduce the direct use of HF and improve operational safety; fluoride / acid system etching can provide milder and more controllable etching conditions; molten salt etching is suitable for etching A-layer elements under high temperature conditions and can obtain products with higher etching degrees; alkaline etching is suitable for alkali-stable MAX phase materials; oxidative etching selectively removes A-layer elements through oxidation reactions; electrochemical etching can achieve more precise etching process control and obtain higher quality MXene products.
[0052] In one feasible implementation, the water content in the low-water and low-oxygen environment is less than 1000 ppm and the oxygen content is less than 1000 ppm; when the physical composite treatment includes mechanical ball milling, the ball-to-material ratio of the mechanical ball milling is (5~100):1, the ball milling speed is 100 r / min~800 r / min, and the ball milling time is 0.1 h~24 h.
[0053] In this technical solution, by controlling the water content and oxygen content to below 1000 ppm and below 1000 ppm in a low-water, low-oxygen environment, the decomposition or formation of a surface oxide layer of aluminum hydride due to contact with moisture and oxygen during mixing and compounding is prevented, thus ensuring the purity and activity of the product. By controlling the ball-to-material ratio of mechanical ball milling to 5:1~100:1, the ball milling speed to 100 r / min~800 r / min, and the ball milling time to 0.1 h~24 h, sufficient grinding and mixing effects are ensured while avoiding over-milling and material structure damage caused by excessively high ball-to-material ratios, speeds, or times.
[0054] Preferably, the protective effect is more significant when the water content is below 100 ppm and the oxygen content is below 100 ppm. More preferably, the highest level of protection can be achieved when the water content is below 10 ppm and the oxygen content is below 10 ppm, ensuring the optimization of material performance.
[0055] Preferably, controlling the ball-to-material ratio of the mechanical ball mill to be 20:1 to 60:1, the ball milling speed to be 300 r / min to 600 r / min, and the ball milling time to be 0.5 h to 6 h is beneficial to achieving uniform dispersion and full compounding of the catalyst.
[0056] The method for preparing aluminum hydride doped with high-entropy MXene provided in this application is used to prepare aluminum hydride doped with high-entropy MXene as described in any of the above technical solutions. Therefore, the method for preparing aluminum hydride doped with high-entropy MXene has all the beneficial effects of the aluminum hydride doped with high-entropy MXene described in the above technical solutions, and will not be elaborated here.
[0057] According to a third aspect of this application, a method for releasing hydrogen from a high-entropy MXene-doped aluminum hydride material is proposed, applicable to any of the high-entropy MXene-doped aluminum hydride materials described in the above technical solutions, comprising: in the thermal decomposition hydrogen release stage of the material, placing the material in a reactor and heating it under inert atmosphere, vacuum, low pressure, normal pressure or a set back pressure, causing the aluminum hydride components to undergo thermal decomposition and release hydrogen, obtaining thermal decomposition products; in the hydrolysis hydrogen supply stage of the thermal decomposition products, adding water or an aqueous reaction medium to the thermal decomposition products, causing the metal hydride and / or metallic aluminum in the thermal decomposition products to hydrolyze and release hydrogen.
[0058] The hydrogen release method for aluminum hydride materials doped with high-entropy MXene provided in this application combines thermal decomposition and hydrolysis hydrogen supply into a continuous hydrogen supply route within the same material system, enabling full utilization of the hydrogen that can be released at different stages in the aluminum hydride material. In the thermal decomposition hydrogen release stage, the material is placed in a reactor and heated to 60°C~200°C under inert atmosphere, vacuum, low pressure, normal pressure, or a predetermined back pressure. Under the catalytic action of the high-entropy MXene catalyst component, the activation energy of the Al-H bond in the aluminum hydride is significantly reduced, causing the aluminum hydride to undergo thermal decomposition and release the first stage of hydrogen gas, achieving rapid hydrogen release at low temperature. After thermal decomposition, the aluminum hydride is converted into thermal decomposition products containing metal hydrides and metallic aluminum. In the hydrolysis hydrogen supply stage, water or an aqueous reaction medium is added to the thermal decomposition products. At a temperature of 10℃ to 60℃, the residual metal hydrides, aluminum, or combinations thereof in the thermal decomposition products undergo further hydrolysis, releasing a second stage of hydrogen. During this process, the metal hydrides react with water to generate hydrogen and alkaline products. The resulting alkaline environment promotes the destruction or dissolution of the passivation layer on the aluminum surface, allowing the aluminum to further participate in hydrolysis to produce hydrogen. Through this two-stage hydrolysis reaction, the hydrolyzable components in the thermal decomposition products are fully utilized, effectively increasing the release rate of usable hydrogen from aluminum hydrides. Simultaneously, the hydrolysis hydrogen supply temperature is controlled at 10℃ to 60℃, achieving efficient hydrolysis hydrogen supply at or near room temperature without additional heating. This reduces the energy consumption and operating costs of the hydrogen supply system, while improving its safety and portability.
[0059] Understandably, aluminum hydride materials doped with high-entropy MXene can be used for hydrogen supply through aluminum hydride thermal decomposition, as well as for hydrogen supply through water-triggered hydrolysis of thermal decomposition products. These high-entropy MXene-doped aluminum hydride materials can be used in powder form, or prepared as granules, tablets, blocks, fuel tablets, or packed molded products.
[0060] The hydrogen release method for aluminum hydride materials doped with high-entropy MXene provided in this application embodiment, since it is applied to aluminum hydride materials doped with high-entropy MXene as described in any of the above technical solutions, has all the beneficial effects of the aluminum hydride materials doped with high-entropy MXene described in the above technical solutions, and will not be elaborated here.
[0061] According to the fourth aspect of this application, an application of an aluminum hydride material doped with high-entropy MXene is proposed. Based on the aluminum hydride material doped with high-entropy MXene as described in any of the above technical solutions, the material is used as a powder hydrogen storage material, a catalytic hydrogen storage material, a molded hydrogen storage material, a hydrogen supply filler, a water injection hydrogen production fuel cell, a hydrogen supply module, or a hydrogen source unit.
[0062] The application of the high-entropy MXene-doped aluminum hydride material provided in this application combines the thermal decomposition of aluminum hydride with the hydrolysis utilization of its decomposition products. It can be used in portable hydrogen supply devices, fuel cell auxiliary hydrogen supply systems, emergency hydrogen supply devices, mobile power supply hydrogen supply units, and hydrogen generators, demonstrating promising industrial application prospects. The material can be used as a powdered hydrogen storage material, catalytic hydrogen storage material, molded hydrogen storage material, hydrogen supply filler, water-injected hydrogen production fuel cell, hydrogen supply module, or hydrogen source unit, exhibiting significant industrialization and application expansion value. Specifically, the material can be applied to solid-state hydrogen storage, storing hydrogen in a solid form, which offers higher volumetric hydrogen storage density and better safety compared to high-pressure gaseous hydrogen storage and cryogenic liquid hydrogen storage; it can be applied to aluminum hydride thermal decomposition, utilizing the catalytic effect of high-entropy MXene to lower the thermal decomposition temperature of aluminum hydride and increase the hydrogen supply rate; it can be applied to hydrogen supply through the hydrolysis of thermal decomposition products, further converting hydrolyzable components, which are traditionally treated as waste residue, into hydrogen by triggering hydrolysis of thermal decomposition products with water injection, thereby maximizing the utilization of hydrogen resources; and it can be applied to portable hydrogen supply, as the material has high hydrogen storage capacity, mild hydrogen supply conditions, and flexible hydrogen supply methods, making it suitable for outdoor power supplies, portable electronic devices, and other applications with low requirements for volume, weight, and ease of operation. High application scenarios: It can be applied to the field of fuel cell hydrogen supply, providing a continuous and stable hydrogen supply to fuel cells by controlling the rate of thermal decomposition and / or hydrolysis reactions; it can be applied to the field of emergency hydrogen supply, enabling rapid hydrogen supply through heating or water injection triggering in scenarios such as natural disasters and wilderness rescue without external power sources or complex equipment; it can be applied to water injection-triggered hydrogen generators, which can start the hydrolysis hydrogen supply reaction by injecting water, with advantages such as rapid start-up, simple operation, and on-demand control of hydrogen supply; it can be applied to the resource utilization of thermal decomposition products of metal hydrides, using the products after thermal decomposition of aluminum hydrides as a secondary hydrogen source, improving the utilization efficiency and economic benefits of materials; it can be applied to hydrogen energy systems as a hydrogen source unit for distributed hydrogen supply systems, mobile hydrogen supply systems, or backup hydrogen supply systems.
[0063] The application of the aluminum hydride material doped with high-entropy MXene provided in this application embodiment is based on the aluminum hydride material doped with high-entropy MXene as described in any of the above technical solutions. Therefore, the application of the aluminum hydride material doped with high-entropy MXene has all the beneficial effects of the aluminum hydride material doped with high-entropy MXene as described in the above technical solutions, which will not be elaborated here.
[0064] Example: Example 1: Ti-V-Cr-Nb-Mo based M2CT x Preparation of high-entropy MXene-doped LiAlH4 composite powder (sample 3) Under an inert atmosphere, a Ti-V-Cr-Nb-Mo high-entropy MAX phase material was provided. A-layer elements were selectively etched away, and the material was then washed, centrifuged, and dried to obtain multilayered Ti sheet-like materials. 0.4 V 0.4 Cr 0.4 Nb 0.4 Mo 0.4 CT x High-entropy MXene catalyst components, such as Figure 3 As shown.
[0065] The dried LiAlH4 powder and the high-entropy MXene catalyst component were transferred to an inert atmosphere ball mill jar, and the mass percentage of the high-entropy MXene catalyst component relative to LiAlH4 was controlled to be 2 wt.%, 5 wt.%, 8 wt.%, or 12 wt.%. Mechanical ball milling was performed under an Ar atmosphere to distribute the high-entropy MXene catalyst component on the surface and between the LiAlH4 particles, forming an interfacial composite material.
[0066] The resulting composite powder, used as Sample 1, underwent thermal decomposition testing under heating conditions to evaluate the effects of the high-entropy MXene catalyst component on the low-temperature thermal decomposition temperature, decomposition amount, and decomposition rate of LiAlH4. The thermally decomposed products were stored under an inert atmosphere and used for subsequent water injection hydrolysis hydrogen donation tests. The temperature-programmed dehydrogenation curve is shown below. Figure 4 and Figure 5 As shown.
[0067] Example 2: Ti-V-Cr-Nb-Mo system M3C2T x Preparation of high-entropy MXene-doped LiAlH4 composite powder Under an inert atmosphere, a Ti-V-Cr-Nb-Mo high-entropy MAX phase material was provided. A-layer elements were selectively etched away, and the material was then washed, centrifuged, and dried to obtain multilayered Ti sheet-like materials. 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6 C2T x High-entropy MXene catalyst components.
[0068] The dried LiAlH4 powder and the high-entropy MXene catalyst component were transferred to an inert atmosphere ball mill jar, and the mass percentage of the high-entropy MXene catalyst component relative to LiAlH4 was controlled to be 2 wt.%, 5 wt.%, 8 wt.%, or 12 wt.%. Mechanical ball milling was performed under an Ar atmosphere using Ti. 0.6 V 0.6 Cr 0.6 Nb 0.6 Mo 0.6C2T x High-entropy MXene catalyst component replaces M2CT in Example 1 x High-entropy MXene catalysts are distributed on the surface and between LiAlH4 particles, forming surface and interfacial composites. The scanning electron microscope (SEM) image of the composite powder material with a mass percentage of 5 wt.% is shown below. Figure 1 As shown.
[0069] The resulting composite powder can be subjected to thermal decomposition tests under heating conditions to compare with M3C2T. x Type and M2CT x The effects of different high-entropy MXene structural types on the low-temperature thermal decomposition temperature, decomposition amount, decomposition rate, and hydrogen supply from the hydrolysis of thermal decomposition products of LiAlH4 were investigated. The thermally decomposed products were stored under an inert atmosphere and used for subsequent water injection hydrolysis hydrogen supply tests.
[0070] Example 3: Preparation of other multi-principal-component high-entropy MXene-doped aluminum hydride composite materials Under an inert atmosphere, high-entropy MAX phase materials of Ti-V-Nb-Mo-Ta, Ti-Zr-Hf-Nb-Ta, Ti-V-Cr-Mo-W, Ti-V-Fe-Co-Ni, or Ti-V-Cr-Nb-Mo-Ta systems were provided. The A-layer elements were removed by selective etching, and the materials were then washed, centrifuged, and dried to obtain the corresponding high-entropy MXene catalyst components.
[0071] The dried LiAlH4 powder and high-entropy MXene catalyst components were transferred to an inert atmosphere ball mill jar, with the mass percentage of the high-entropy MXene catalyst component relative to LiAlH4 controlled at 2 wt.%, 5 wt.%, 8 wt.%, or 12 wt.%. Mechanical ball milling was performed under an Ar atmosphere to distribute the high-entropy MXene catalyst component on the surface and between the LiAlH4 particles, forming an interfacial composite material. Following the same ball milling composite method, NaAlH4, AlH3, Mg(AlH4)2, or Ca(AlH4)2 were used to replace LiAlH4 as the aluminum hydride component, and composited with the aforementioned high-entropy MXene catalyst components to obtain different high-entropy MXene-doped aluminum hydride composite materials.
[0072] The resulting composite powder can be subjected to thermal decomposition tests under heating conditions to evaluate the effects of different elemental combinations of high-entropy MXene catalyst components on the low-temperature thermal decomposition temperature, decomposition amount, and decomposition rate of different aluminum hydrides. The products after thermal decomposition are stored under an inert atmosphere and used for subsequent water injection hydrolysis hydrogen supply tests. This embodiment illustrates that the high-entropy MXene metal site combination of the present invention is not limited to the five elements Ti, V, Cr, Nb, and Mo, and the types of aluminum hydrides are not limited to LiAlH4.
[0073] Example 4: Preparation of aluminum hydride tablets or fuel pellets doped with high-entropy MXene Under an inert atmosphere, the high-entropy MXene / LiAlH4 composite powder obtained in Example 1 or Example 2 is placed in a tableting mold and a pressure of 1MPa to 200MPa is applied to obtain a sheet-like, block-like, or fuel-sheet-like aluminum hydride molded body doped with high-entropy MXene.
[0074] The molded body may be free of binder, or a small amount of binder, thermally conductive agent, electrically conductive agent, pore-forming agent, or molding aid may be added as needed. This molded body can be directly used for thermal decomposition tests to examine the effects of high-entropy MXene catalyst components on the low-temperature thermal decomposition temperature, decomposition amount, and decomposition rate of LiAlH4. It can also be used to perform water injection, dripping, spraying, or pumping hydrolysis hydrogen donation tests on the products after thermal decomposition to evaluate the influence of the molded body morphology on thermal decomposition and hydrolysis hydrogen donation behavior.
[0075] Example 5: Thermal decomposition and its product hydrolysis hydrogen donation method The composite material obtained in Example 1 or Example 2 is placed in a closed or semi-closed decomposition reactor and heated to a set temperature under an inert atmosphere to cause LiAlH4 to undergo a thermal decomposition reaction, releasing first-stage hydrogen and forming thermal decomposition products mainly containing LiH and Al.
[0076] After thermal decomposition is complete, under conditions of minimal or no air exposure, deionized water, alkaline aqueous solution, salt solution, alcohol-water mixture, or other aqueous reaction medium are added to the thermal decomposition products. This causes LiH to hydrolyze, generating LiOH and H2. The resulting LiOH provides an alkaline environment, which promotes the destruction, dissolution, or transformation of the oxide or hydroxide passivation layer on the Al surface, allowing Al to further participate in hydrolysis to donate hydrogen and release hydrogen gas in the second stage.
[0077] This embodiment demonstrates that the efficient decomposition route of the present invention includes two main stages: thermal decomposition and hydrogen donation through hydrolysis of thermal decomposition products. In this process, high-entropy MXene not only promotes the thermal decomposition of aluminum hydrides, but also promotes hydrogen donation through hydrolysis of products via interface wetting, hydrophilic end groups, and multi-metal active sites.
[0078] Comparative Example 1: LiAlH4 (sample 1) without MXene doping Under the same ball milling, thermal decomposition, and hydrolysis hydrogen donation conditions as in Example 1, without the addition of high-entropy MXene catalyst components, only pure LiAlH4 was used as a comparative material (i.e., blank control) to illustrate the effects of high-entropy MXene catalyst components on thermal decomposition temperature, decomposition rate, and hydrolysis hydrogen donation behavior of thermal decomposition products. The temperature-programmed dehydrogenation curves are shown below. Figure 4 and Figure 5 As shown.
[0079] Comparative Example 2: LiAlH4 (Sample 2) doped with conventional MXene material Under the same conditions as in Example 1, Ti3C2T was used. x Ti2CT x Alternatively, other non-high-entropy MXenes were used to replace the high-entropy MXene catalyst components, and ball-milled with LiAlH4 as a comparative material. Thermal decomposition and hydrolysis hydrogen donation tests were performed on this comparative material to illustrate the synergistic catalytic effect of the multi-metal sites and localized electronic structure in high-entropy MXene compared to traditional MXene. Its temperature-programmed dehydrogenation curve is shown below. Figure 4 .
[0080] Comparative Example 3: Thermal Decomposition Only High-entropy MXene / LiAlH4 composite powder was prepared according to the basic method of Example 1. The resulting composite powder was placed in a reactor and heated for thermal decomposition under the same thermal decomposition conditions as in Example 1. However, after the thermal decomposition was completed, no water or aqueous reaction medium was added to the resulting thermal decomposition products. This was used as a comparative example to illustrate that without the hydrolysis hydrogen supply step, the hydrogen resources contained in the metal hydrides (such as LiH) and aluminum (Al) in the thermal decomposition products cannot be released, resulting in a significant reduction in the release of usable hydrogen in the system.
[0081] Figure 4 The high-entropy MXene / LiAlH4-5wt.% composite powder (sample 3) prepared in Example 1 of this application, compared with Comparative Example 1 (pure ball-milled LiAlH4, sample 1) and Comparative Example 2 (doped with ordinary MXene Ti3C2T) x Comparison of temperature-programmed dehydrogenation curves for -5wt.% LiAlH4, sample 2). Figure 4 It can be seen that Sample 1 has the highest initial decomposition temperature and obvious stepwise decomposition characteristics; the initial decomposition temperature of Sample 2 is lower than that of Sample 1, but still higher than that of Sample 3; Sample 3 has the lowest initial decomposition temperature and the fastest hydrogen release rate. This indicates that high-entropy MXene can effectively reduce the thermal decomposition temperature of aluminum hydride and increase the hydrogen supply rate, and its catalytic effect is better than that of ordinary MXene, demonstrating the synergistic catalytic advantage of high-entropy MXene's multi-metal sites.
[0082] Figure 5 A comparison of the temperature-programmed dehydrogenation and subsequent hydrolysis dehydrogenation curves of the high-entropy MXene / LiAlH4-5wt.% composite powder prepared in Example 1 (sample 3) and Comparative Example 1 (pure ball-milled LiAlH4, sample 1). Figure 5 As can be seen, the curve contains two hydrogen release stages: the first stage is the thermal decomposition stage, lasting 150 min, where aluminum hydride from sample 1 decomposes and releases hydrogen under the catalysis of high-entropy MXene; the second stage is the hydrolysis hydrogen supply stage, lasting 100 min, where metal hydrides and metallic aluminum in the thermal decomposition products react with water to further release hydrogen. The two-stage hydrogen supply route of thermal decomposition and hydrolysis in this application significantly improves the cumulative hydrogen release. The cumulative hydrogen release after thermal decomposition and hydrolysis of the thermal decomposition products can reach over 18 wt.%, and the hydrogen supply rate can reach 44.6 mmol·min. -1 ·g -1 .
[0083] It will be readily understood by those skilled in the art that the above embodiments can be freely combined and superimposed without conflict.
[0084] The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application. The above are merely preferred embodiments of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of this application, and these improvements and modifications should also be considered within the protection scope of this application.
Claims
1. An aluminum hydride material doped with high-entropy MXene, characterized in that, The aluminum hydride material doped with high-entropy MXene includes: The aluminum hydride component and the high-entropy MXene catalyst component are present, wherein the high-entropy MXene catalyst component is at least partially distributed on the particle surface, interparticle space, grain boundary or interface region of the aluminum hydride component, and the high-entropy MXene catalyst component forms a physical composite with the aluminum hydride component. The high-entropy MXene catalyst component is used to promote the activation and breaking of Al-H bonds during the thermal decomposition of the aluminum hydride component, and to promote the hydrolysis and hydrogen supply of the thermal decomposition products after contact with water or an aqueous reaction medium. The physical composite includes at least one of ball milling composite, surface composite, interface composite, coating composite, embedding composite, slurry composite, granulation composite, and molding composite.
2. The aluminum hydride material doped with high-entropy MXene according to claim 1, characterized in that: The high-entropy MXene catalyst components are multilayer sheet structures, few-layer sheet structures, single-layer sheet structures, accordion-like layer structures, exfoliated sheet structures, wrinkled sheet structures, nanosheet stacked structures, or porous sheet structures.
3. The aluminum hydride material doped with high-entropy MXene according to claim 1, characterized in that: The chemical formula of the high-entropy MXene catalyst component is represented by M. n+1 X n T x ; Wherein, M is a metal site element, and M is selected from at least four of the metal elements in Groups IIIB, IVB, VB, VIB, VIIB, VIII, IB and IIB of the periodic table and the lanthanide metal elements; X is a combination of one or more of C, N and B; T x As a surface end base, the T x It is a combination of one or more of O, F, Cl, Br, I and OH; n can be 1, 2, 3, 4, 5, or 6.
4. The aluminum hydride material doped with high-entropy MXene according to claim 3, characterized in that: The M includes at least four of the following elements: Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Re, Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, Au, Zn, Cd, and lanthanides.
5. The aluminum hydride material doped with high-entropy MXene according to claim 2, characterized in that: The aluminum hydride component includes at least one of LiAlH4, NaAlH4, AlH3, Li3AlH6, Na3AlH6, and Mg(AlH4)2; The high-entropy MXene catalyst component includes M2CT. x Model, M3C2T x Type, M4C3T x Model, M5C4T x Type, M2NT x Type, M3N2T x Type and M2BT x At least one of the types; The high-entropy MXene catalyst component has a mass percentage of 0.1 wt.% to 50 wt.% relative to the aluminum hydride component.
6. A method for preparing an aluminum hydride material doped with high-entropy MXene, characterized in that, A method for preparing an aluminum hydride material doped with high-entropy MXene as described in any one of claims 1 to 5, wherein the method for preparing the aluminum hydride material doped with high-entropy MXene comprises: Post-processing of high-entropy MXene catalyst components; In an inert atmosphere, vacuum, or low-water, low-oxygen environment, the aluminum hydride component is mixed with the high-entropy MXene catalyst component to obtain a mixture; The mixture is subjected to physical composite treatment so that the high-entropy MXene catalyst component is at least partially distributed on the particle surface, interparticle gaps, grain boundaries or interface regions of the aluminum hydride component; The physical composite treatment includes at least one of mechanical ball milling, grinding, mixing, kneading, shearing dispersion, granulation, tableting, rolling and forming.
7. The method for preparing an aluminum hydride material doped with high-entropy MXene according to claim 6, characterized in that, Prior to the post-treatment of the high-entropy MXene catalyst components, the following steps are also included: Provide a high-entropy MAX phase precursor or the high-entropy MXene catalyst component; When a high-entropy MAX phase precursor is provided, the high-entropy MAX phase precursor is selectively etched to remove at least some of the A-layer elements to obtain the high-entropy MXene catalyst component. The selective etching process includes at least one of HF etching, HCl / LiF etching, fluoride / acid system etching, molten salt etching, alkaline etching, oxidative etching, and electrochemical etching.
8. The method for preparing an aluminum hydride material doped with high-entropy MXene according to claim 6, characterized in that: The water content and oxygen content in the low-water and low-oxygen environment are less than 1000 ppm and less than 1000 ppm, respectively. When the physical composite treatment includes mechanical ball milling, the ball-to-material ratio of the mechanical ball milling is (5~100):1, the ball milling speed is 100r / min~800r / min, and the ball milling time is 0.1h~24h.
9. A method for releasing hydrogen from an aluminum hydride material doped with high-entropy MXene, characterized in that, Applied to an aluminum hydride material doped with high-entropy MXene as described in any one of claims 1 to 5, the method for releasing hydrogen from the aluminum hydride material doped with high-entropy MXene comprises: In the thermal decomposition and hydrogen release stage of the material, the material is placed in a reactor and heated under inert atmosphere, vacuum, low pressure, normal pressure or set back pressure conditions to cause the aluminum hydride component to undergo thermal decomposition and release hydrogen gas, thereby obtaining thermal decomposition products. In the hydrogen supply stage of hydrolysis of thermal decomposition products, water or an aqueous reaction medium is added to the thermal decomposition products to hydrolyze the metal hydrides and / or aluminum in the thermal decomposition products and release hydrogen gas.
10. An application of an aluminum hydride material doped with high-entropy MXene, characterized in that, Based on the aluminum hydride material doped with high-entropy MXene as described in any one of claims 1 to 5, the applications of the aluminum hydride material doped with high-entropy MXene include: The material is used as a powder hydrogen storage material, catalytic hydrogen storage material, molded hydrogen storage material, hydrogen supply filler, water injection hydrogen production fuel pellet, hydrogen supply module or hydrogen source unit.